Recidivism Policy in the National Criminal Code: Sanctions and Rehabilitation - Harya Juang Siregar; Adi Mansar (Yayasan Abdurrauf Cendekia Nusantara, 2026)
This study analyzes criminal law policies towards recidivism from the perspective of the principle of increased sanctions and the rehabilitative objectives of punishment in Law Number 1 of 2023 concerning the Criminal Code. Using normative juridical methods and a legislative approach, this study examines the paradigm shift from a retributive model to a more humanistic and proportional approach. The National Criminal Code regulates general recidivism with the possibility of increasing the sentence to one-third of the maximum threat, but still places it within the framework of criminal objectives that include prevention, development, and restoration of social balance. The results of the study indicate that policies towards recidivism are no longer solely repressive, but are integrated with the principle of individualization of punishment and a rehabilitative approach strengthened by the correctional system in Law Number 22 of 2022 concerning Corrections. This reorientation emphasizes the balance between community protection and reintegration of offenders to reduce recidivism sustainably. [Penelitian ini menganalisis kebijakan hukum pidana terhadap residivisme dari perspektif prinsip pemberatan pidana dan tujuan rehabilitatif pemidanaan dalam Undang-Undang Nomor 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana. Dengan menggunakan metode yuridis normatif dan pendekatan perundang-undangan, penelitian ini mengkaji pergeseran paradigma dari model retributif menuju pendekatan yang lebih humanistis dan proporsional. KUHP Nasional mengatur residivisme umum dengan kemungkinan pemberatan pidana hingga sepertiga dari ancaman pidana maksimum, namun tetap menempatkannya dalam kerangka tujuan pemidanaan yang mencakup pencegahan, pembinaan, dan pemulihan keseimbangan sosial. Hasil penelitian menunjukkan bahwa kebijakan terhadap residivisme tidak lagi semata-mata bersifat represif, melainkan terintegrasi dengan prinsip individualisasi pemidanaan dan pendekatan rehabilitatif yang diperkuat melalui sistem pemasyarakatan sebagaimana diatur dalam Undang-Undang Nomor 22 Tahun 2022 tentang Pemasyarakatan. Reorientasi ini menekankan keseimbangan antara perlindungan masyarakat dan reintegrasi pelaku tindak pidana guna mengurangi tingkat residivisme secara berkelanjutan.]